Formation of Communicative Culture of Students by Means of Project Teaching in Higher Educational Establishments - Maksymenko, Nataliia; Bei, Iryna; Khimchuk, Liliana; Vovchok, Yaroslav (Journal of History Culture and Art Research, 2020)
The article is devoted to the problem of forming the communicative culture of future teachers in the process of project teaching in higher educational establishments. Methodological approaches to the definition of the concept of "communicative culture" are analyzed, its qualitative characteristics are determined and examples of discussions in the scientific environment on the characteristics of this phenomenon are given. The authors claim that the component of communicative culture is communicative competence, which in the educational process of higher education largely determines the quality of training of future teachers for future professional activities. The article gives the hypothesis that project activities may be one of the effective means of forming both communicative culture and communicative competence, which at the present stage of training graduate students is considered the most effective and rational in domestic and foreign pedagogy. In order to test the hypothesis, the results of the diagnostic stage of the experimental study conducted during the training of future foreign language teachers in higher educational establishments are demonstrated. The analysis of the results of the experiment allowed us to conclude that project teaching is defined by both students and teachers as one of the effective means of forming the communicative culture of future graduate students. Its significance is determined by the fact that it allows students to thoroughly analyze scientific information, use a creative approach to learning materials, promote the formation of skills to listen to others, respect alternative opinions, model and solve cognitive, life and social situations.